AVALIAÇÃO POR MEIO DE MODELOS VIRTUAIS TRIDIMENSIONAIS DAS DISTÂNCIAS INTERCANINOS E INTERMOLARES INFERIORES EM TRÊS MOMENTOS - Viek, Roberto (2008)
The purpose of this study was to evaluate the stability of the orthodontic treatment in three distinct moments, by measuring the inferior intercanine and intermolar widths using three-dimensional virtual models as tools. Inferior arch cast models of 19 patients in three distinct phases were selected, pretreatment (T1), post treatment (T2) and minimum of 5 years post-contention (T3), adding up to 57 models, which were digitalized through Scanner 3D SCANTEH ST500 (SCAN technology A/S, CITY, Denmark), to obtain three-dimensional virtual models. In these three-dimensional virtual models, the distances between cuspids of the canines, called intercanine width and the distance between cuspids mesio-buccal of the first molars, called intermolar width, were selected and measured with the help of the software Rapidform (Inus Technology Inc). In order to do a statistical analysis, the analysis of variance of repeated measures was performed, and also, multiple comparisons of Bonferroni at significance level of 5% were performed. The intercanine and intermolar widths, on an average, decreased between T1-T2 and kept on decreasing between T2-T3. After 4 weeks, 20% of the sample was measured again to evaluate the fault of the method, where we can find average values similar to the ones found in the first measuring. In this study, by using threedimensional virtual models, it is possible to notice that there is no stability during and after the orthodontic treatment, concerning intercanine and intermolar widths.(AU)